Pengakuan Status Anak Luar Kawin dalam Perspektif Hukum Islam dan Hukum Positif - Rahman, Yahya Ibadu; Abidin, Zainal; ., Isfihani (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This study aims to analyze the differences and gaps between Islamic law and positive law in Indonesia regarding the status and rights of illegitimate children, particularly in matters of lineage, inheritance, and guardianship. It also explores the legal and social implications faced by illegitimate children and formulates efforts for regulatory harmonization to protect their rights more fairly and comprehensively. The research employs normative or dogmatic legal methods, focusing on the analysis of primary legal materials such as the Qur'an, Hadith, Marriage Law, and Constitutional Court decisions, along with secondary legal materials including scholarly literature and supporting documents. The findings reveal fundamental differences in the recognition of the rights of illegitimate children between the two legal systems. Islamic law limits lineage and inheritance rights to the mother, whereas positive law provides opportunities for recognizing civil relationships with the biological father. The social implications of this status include stigma, discrimination, and limited access to basic rights. Therefore, harmonization between Islamic law and positive law is necessary, through cross-sectoral dialogue and regulatory reform, to ensure comprehensive protection of children's rights.